The Difference of Ultra-Processed Food Consumption based on Individual Characteristics and Other Factors among Non-Health Undergraduate Students in Universitas Indonesia in 2023 - Adeline Vashtianada; Asih Setiarini; Ratu Ayu Dewi Sartika (Indonesian Journal of Public Health Nutrition (IJPHN), 2023)
Ultra-processed food/UPF is a product that undergoes a series of industrial techniques and processes, also has low nutritional value. Overconsumption of UPF can increase the risk of overweight and obesity. The purpose of this study is to determine the differences in the proportion of UPF consumption based on individual characteristics, environmental factors, and lifestyle factors among non-health undergraduate students in Universitas Indonesia in 2023. A cross sectional study design conducted on 149 samples. The data was collected using a self-administered online questionnaire. The data was analyzed using univariate and bivariate (chi-square) analyses. The results showed that 50,3% of the students consumed a high level of UPF. The bivariate analysis showed a significant difference in the proportion of UPF consumption based on peer influence and access to UPF.